Programming and controlling robots using scanning on a speech generating communication device: A case study. - Adams, Kim D.; Cook, Albert M. (Technology & Disability, 2013)
BACKGROUND: Programming Lego Mindstorms robots is used for problem-based learning in science. Children with physical disabilities and complex communication needs may be limited in their ability to participate.OBJECTIVES: To involve a 12 year old student with cerebral palsy in programming Lego robots in the classroom by using her speech generating device (SGD). To evaluate the effectiveness and efficiency of using the two-switch scanning mode on the SGD for programming. METHODS: The participant tested classmates' robot programs using infrared on her SGD, and she accessed the programming software via a customized mouse manipulation page. Her participation in programming activities was measured with Goal Attainment Scaling, descriptive observations, and measures of effectiveness and efficiency. RESULTS: The participant progressed from observing classmates to independently testing robot programs in the classroom. In individualized sessions she wrote a simple program, with support. Limitations in scanning led to unwanted cursor movements and long task times.CONCLUSIONS: The participant actively participated in the robot programming activity. Actually programming was better suited to individual instruction because of her scanning inefficiency. Using the SGD for robot control affords the potential to also discuss concepts, but this novice user did not yet have the skills to utilize this aspect.